MIDWIFERY CARE FOR POSTPARTUM MOTHERS WITH OXYTOCIN MASSAGE INTERVENTION FOCUS ON LACTATION PROSES AT PURWODADI PUBLIC HEALTH CENTER 1 - Dewi Andriani Putri; Nurul Kodiyah; Dhiyan Nany Wigati (The Shine Cahaya Dunia Kebidanan, 2023)
Background; Postpartum is the period of 6 weeks or 42 days after delivery. Similar to pre- pregnancy, the reproductive organs will undergo gradual changes. 60% of maternal morbidity occurs during the puerperium. These statistics explain the number of postpartum deaths. (Handayani, 2021). Oxytocin massage is one approach that can be used to overcome the problem of uneven milk production. Oxytocin massage is a type of massage performed along the spine (vertebrates) to the fifth or sixth rib. .This massage aims to increase the hormones prolactin and oxytocin released after childbirth. Oxytocin massage has a number of benefits, including providing comfort to the mother and stimulating the oxytocin reflex. Method; The research design that the researcher uses is a case study research design. This type of descriptive case study research uses participatory observation method. The subjects in this study were postpartum mothers. Result; The results of the study showed that the diagnosis in Mrs. G was that breast milk was not smooth. Evaluation of the implementation of oxytocin massage in the case of Mrs. G with non-fluent breast milk, it was found that the milk had come out smoothly. Conclusion; The problem of breastfeeding is not smooth, Mrs. G has been resolved.